(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, opinions on increasing the activity of introducing educational standards based on a new approach to the training of future physical education teachers, on awakening a sense of responsibility for the chosen profession, on the development of various reforms in society are presented.